Elucidating Mechanisms of Endophytes Used in Plant Protection and Other Bioactivities With Multifunctional Prospects - Fadiji, Ayomide Emmanuel; Babalola, Olubukola Oluranti (Frontiers in Bioengineering and Biotechnology, 2020)
Endophytes are abundant in plants and studies are continuously emanating on their ability to protect plants from pathogens that cause diseases especially in the field of agriculture. The advantage that endophytes have over other biocontrol agents is the ability to colonize plant’s internal tissues. Despite this attributes, a deep understanding of the mechanism employed by endophytes in protecting the plant from diseases is still required for both effectiveness and commercialization. Also, there are increasing cases of antibiotics resistance among most causative agents of diseases in human beings, which calls for an alternative drug discovery using natural sources. Endophytes present themselves as a storehouse of many bioactive metabolites such as phenolic acids, alkaloids, quinones, steroids, saponins, tannins, and terpenoids which makes them a promising candidate for anticancer, antimalarial, antituberculosis, antiviral, antidiabetic, anti-inflammatory, antiarthritis, and immunosuppressive properties among many others, even though the primary function of bioactive compounds from endophytes is to make the host plants resistant to both abiotic and biotic stresses. Endophytes still present themselves as a peculiar source of possible drugs. This study elucidates the mechanisms employed by endophytes in protecting the plant from diseases and different bioactivities of importance to humans with a focus on endophytic bacteria and fungi.